Coupled systems of integro-differential equations involving Riemann-Liouville integrals and Caputo derivatives - Dahmani, Zoubir; Houas, Mohamed (Acta Univ. Apulensis Math. Inform, 2014)
A coupled system of fractional integro-differential equations involv- ing Riemann-Liouville integral and Caputo derivative is considered in this paper. Some existence and uniqueness results are obtained using Banach contraction prin- ciple. Other existence results are also studied using Shaefer’s fixed point theorem. At the end, some illustrative examples are discussed.
Keywords: Coupled system, Caputo derivative, Riemann-Liouville integral, Ex- istence, Fixed point theorem.